The Efficacy of Mediterranean Diet for Erectile Dysfunction in Diabetes Mellitus Patients: A Narrative Review - Atmaja, Maxwell; Purnama, Michael; Kevin, Kevin; Aslama, Fathiy Zakaria; Rizkiliano, Ibrahim Hanif; Sudana, Nathan Kunta; I'tishom, Reny (Indonesian Andrology and Biomedical Journal, 2024)
Background : Male infertility affects millions globally, with 12-15% of Indonesian couples facing conception challenges, 50% of which are attributed to male factors. Despite extensive research, 70% of male infertility cases remain idiopathic. Diabetes, a prominent factor in male infertility, affects 9.3% of the global population, with projections estimating 700 million cases by 2045. Recent studies suggest the Mediterranean diet positively impacts semen parameters, particularly in diabetic individuals. This review aims to explore the Mediterranean diet's effects on fertility in male diabetic patients. Reviews : The literature review employed three databases, focusing on in-vitro, in-vivo, pre-clinical, and clinical studies from 2014-2024. Diabetes, a chronic disease characterized by abnormal blood sugar levels, affects insulin production or effectiveness, leading to complications if left uncontrolled. Erectile dysfunction (ED), prevalent in diabetic men, is attributed to nerve and blood vessel damage from high blood sugar levels. Treatments for ED include PDE5 inhibitors, but alternative plant-based therapies are being explored. Platelet-rich plasma (PRP) has shown promise in animal studies but lacks human trial data. The Mediterranean diet, rich in plant-based foods and healthy fats, may help prevent sexual function deterioration in diabetic individuals. Comprehensive nutrition education and government efforts are crucial in promoting healthy lifestyles and ensuring access to fresh foods. Summary : In conclusion, the Mediterranean diet shows promise as a dietary intervention for improving male fertility in diabetic populations. Further research is warranted to confirm these findings and to explore the mechanisms underlying the effects of the Mediterranean diet on male fertility.